Max Weber and The Protestant ethic: twin histories - Ghosh, Peter (Oxford University Press, 2014)
Ghosh presents a new portrait of Max Weber, one of the most prestigious social theorists in recent history, using his most famous work, 'The Protestant Ethic and the 'Spirit' of Capitalism', as its central point of reference. It offers an intellectual biography of Weber framed along historical lines. It re-evaluates ''The Protestant Ethic' - a text surprisingly neglected by scholars - supplying a missing intellectual and chronological centre to Weber's life and work